School climate and exposure to bullying: a multilevel study. Issue 1 (2nd January 2017) - Låftman, Sara Brolin; Östberg, Viveca; Modin, Bitte
ABSTRACT: This study investigates associations between aspects of school climate, measured by students' assessments aggregated to the class level, and exposure to bullying, measured at the individual level. The data were derived from the Stockholm School Survey of 2006–2010 with information from 16, 418 ninth-grade students (aged 15–16 years) distributed over 871 classes and 259 schools. Three-level binary logistic regression was applied. Two of the studied school climate aspects in particular were linked with the occurrence of bullying: In classes where a high proportion of students claimed to be aware of the school rules and in classes where a high proportion of students stated that adults intervene against bullying, fewer students reported having been bullied. The findings imply that striving toward a school climate characterized by transparent rules and clear disapproval of harassments may help to reduce bullying.